Conspiracy beliefs in the general population: The importance of psychopathology, cognitive style and educational attainment. (1st December 2019) - Georgiou, Neophytos; Delfabbro, Paul; Balzan, Ryan
Abstract: Conspiracy theories (CT) are belief structures which attribute the causes of events to malevolent forces, often involving multiple actors, to bring about outcomes that serve particular powerful interests or agendas. Two principal explanations are usually advanced to account for these beliefs. One is that CTs arise from deeper psychopathological conditions such as schizotypy that predispose some people to CT reasoning. A second is that people differ in their use and training in analytical reasoning. In this study, we examine relative merit of each explanation in combination in a study involving a general population study of 358 adult participants (210 males, 148 females) drawn principally from North America, the UK and Australia. Participants completed measures of schizotypy, delusion-proneness, stress, educational attainment and cognitive style. The results confirmed all hypotheses. Greater endorsement of specific and general CT beliefs was higher in those with elevated psychopathology scores, lower education and who relied less on analytical thinking. Multiple regression showed that psychopathological factors (schizotypy and delusion-proneness) emerged as the strongest predictors.